Mitigating Risk of Failure by Expanding Family Entrepreneurship and Learning from International Franchising Experiences of Johnny Rockets: A Case Study in Pakistan - Jawaid Ahmed Qureshi; Muhammad Shahid Qureshi; Muhammad Asif Qureshi (International Journal of Experiential Learning & Case Studies)
It is generally believed worldwide and backed by research too that startups face a high risk of failure and eight to nine out of ten ideas may not work (Hisrich, Peters, & Shepherd, 2009). However, many experts claim that the situation can turn vice versa for family entrepreneurship (or creative family businesses) and franchise ventures (Francorp, 2016). This exploratory probe aims to discover these two phenomena for Johnny Rockets (JR) Pakistan, which is an international franchise of fast food chain of restaurants, and simultaneously it is a family business extension. Literature is reviewed from four perspectives: family entrepreneurship and business, franchise business, internationalization of companies, and fast food restaurant industry in Pakistan. Primary data is garnered from three sources: in-depth interviews from middle to top management of Johnny Rockets, owners of the franchises, and from its consumers in accordance with phenomenology method and purposive sampling to analyze their lived experiences with JR and its direct rivals. The data analytic techniques comprise thematic analysis and constant comparison. The findings unveil that in the wake of tolerating several difficulties, now Johnny Rockets seems to be on the right path of sustainable growth. The study underpins the notions that family entrepreneurship and franchise ventures enjoy a high probability of success, but it requires an organizational culture of the congenial work environment, and propensity to create a customer-centric modern learning organization, ready to accept trials and errors and continuously innovating its processes and systems.